Immersive theatre and the aesthetics of decadence: on the ruined worlds of Punchdrunk, SHUNT and Hammer Film Productions. Issue 4 (2nd October 2017) - Alston, Adam
ABSTRACT: This article considers how an aesthetics of decadence underpins approaches to design and audience engagement in work by Punchdrunk, SHUNT and Hammer Film Productions. Punchdrunk's The Masque of the Red Death (2007–08) invited wandering audiences to inhabit the ruinous landscapes of Edgar Allan Poe's short stories, recognised posthumously as 'decadent' fiction. SHUNT's The Boy Who Climbed Out of His Face (2014) guided promenading audiences through a series of discarded shipping containers, each containing a lonesome occupant appearing in a state of disturbing physical decay – a dystopian reflection, perhaps, on the decadence of capitalism. And Hammer Film Productions' Hammer House of Horror Live – The Soulless Ones (2017) staged a macabre homage to Hammer Horror films, complete with necromancy, blood-sucking vampires and orgiastic rituals. In this article, I explore how each performance, in its own way, gestures towards a decadent imagination identified and unpacked in light of criticism that informed its evolution in the nineteenth century, alongside more recent analysis that has reset the parameters of its study. This article also presents a challenge to scholarship that narrows focus to the enervating qualities of immersive theatre by considering ruination and decay as important themes informing the design of each performance, and the engagement of audiences both with and within ruined environments both actual and artificial. I argue that the decadent imagination is of much relevance to the study of aesthetics and politics in work that either sensationalises or questions its atomising tendencies, and that such work has much to offer to how decadence is understood, not just as a mutable concept, but as a radical practice.